Building Sustainable Business Excellence Through Knowledge Management, Innovation, Learning Agility, Talented HR, Organizational Culture as Mediator - Novilda Asril; Zulkifli Zulkifli; Lies Putriana (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The purpose of this research is to analyze the effect of knowledge management, learning agility innovation, talented HR on corporate culture, then analyze the influence of knowledge management, innovation, learning agility, talented HR and corporate culture on the company's sustainability business excellence. In this study the approach used is a quantitative approach. This approach relies more on numbers in the form of scores as an analytical framework where the scores are obtained by the survey method. The population in this study were all BoD-1 level employees (equivalent to Entity Directors General Manager), BoD-2 level (Manager equivalent) and BoD-3 level (Assistant Manager equivalent) at PT XYZ with a sample size of 150 respondents whose data was processed using structural equation modelling. The results of this study indicate that knowledge management has no effect on sustainability business excellence, knowledge management has a significant effect on organizational culture, innovation has a significant effect on sustainability business excellence, innovation has a significant effect on organizational culture, learning agility has no effect on sustainability business excellence, learning agility has a significant effect on organizational culture, Talented HR has a significant effect on the sustainability of Business Excellence, Talented HR has a significant effect on Organizational Culture, Organizational Culture has a significant effect on the sustainability of Business Excellence.